German brass for Benin Bronzes: Geochemical analysis insights into the early Atlantic trade - Skowronek, Tobias B.; DeCorse, Christopher R.; Denk, Rolf; Birr, Stefan D.; Kingsley, Sean; Cook, Gregory D.; Benito Dominguez, Ana María; Clifford, Brandon; Barker, Andrew; Otero, José Suárez; Moreira, Vicente Caramés; Bode, Michael; et al. (PLOS ONE, 2023)
Utilizing geochemical analysis, this study identifies the sources of European brass used in the casting of the renowned Benin Bronzes, produced by the Edo people of Nigeria. It is commonly believed that distinctive brass rings known as “manillas”, used as currency in the European trade in West Africa, also served as a metal source for the making of the Bronzes. However, prior to the current study, no research had conclusively connected the Benin artworks and the European manillas. For this research, manillas from shipwrecks in African, American and European waters dating between the 16th and 19th Century were analysed using ICP-MS analysis. Comparing trace elements and lead isotope ratios of manillas and Benin Bronzes identifies Germany as the principal source of the manillas used in the West African trade between the 15th and 18th centuries before British industries took over the brass trade in the late 18th century.